2017
DOI: 10.1111/jgs.15138
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Prescribing in Older Hospitalized Adults: A Comparison of Medical Specialties

Abstract: This study demonstrates the high and growing prevalence of PIMs in the hospital environment, according to Beers and STOPP criteria. Educational measures and specific pharmaceutical interventions for each specialty are needed to change this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
3
16
1
Order By: Relevance
“…The study population comprised patients discharged from a single medical unit in one hospital and therefore results may not be generalizable to other settings. However, the observed prevalence of PIMs and PPOs in our study is comparable to those reported by others in different patient groups .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The study population comprised patients discharged from a single medical unit in one hospital and therefore results may not be generalizable to other settings. However, the observed prevalence of PIMs and PPOs in our study is comparable to those reported by others in different patient groups .…”
Section: Discussionsupporting
confidence: 90%
“…The higher reported prevalence in the inpatient setting is likely a reflection of greater co‐morbidity and prescription medication burden. Our finding that 59.1% of the study population were subject to one or more PIMs is similar to the proportion reported by others applying version 2 of the STOPP criteria in the inpatient setting .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There is an association between inappropriate prescribing in the elderly and mortality, need for additional healthcare services, adverse drug events, and decreased quality of life (3,4). Several studies were conducted to assess appropriate medication prescription among elderly in different settings including the community (5,6), primary care settings (7,8), nursing homes (9), and hospitals (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%